Luke Whitmore, Mountain, Water, Rock, God: Understanding Kedarnath in the Twenty-first Century - Edelmann, Jonathan (Journal for the Study of Religion, Nature and Culture, 2021)
Luke Whitmore, Mountain, Water, Rock, God: Understanding Kedarnath in the Twenty-first Century (Oakland, CA: University of California Press, 2018), 258 pp., 34.95 (pbk), ISBN: 978-0520298026.